Peran Masyrakat Dalam MPeran masyrakat dalam menjaga moral agar terhindar dari perilaku tercelanjaga Moral Agar Terhindar Dari Perilaku Tercela - Mauludya, Dita (Maliki Interdisciplinary Journal, 2025)
Morality is the main pillar in building a harmonious social life, but despicable behaviors such as greed, cunning, riya', persecution, and discrimination are increasingly prevalent in modern society. This research aims to discuss the role of society in maintaining morality to prevent despicable behavior. The method used is qualitative with a descriptive approach, involving observation of social interactions and data collection from various sources. The results show that families have a dominant role in shaping the moral character of individuals, but many families experience difficulties in implementing effective moral education due to the influence of consumptive culture and individualism. Community participation in maintaining morality varies, with some communities having strong moral education programs. Synergy between individuals, families, educational institutions and public policy is essential in maintaining morality. With social support and exemplary behavior from community leaders, it is hoped that despicable behavior can be minimized and a better social environment can be realized.